Effects of moisture content on the strength of weathered granite in tropical climate - Mohamed Fauzi Md. Isa, 1985-; Edy Tonnizam Mohamad; Mohd. For Mohd. Amin, supervisor; Fakulti Kejuruteraan Awam (2011)
Thesis (Sarjana Kejuruteraan (Awam - Geoteknik)) - Universiti Teknologi Malaysia, 2011